THE IMPORTANCE OF THE DIGITAL ECONOMY IN UZBEKISTAN AND ITS IMPACT ON ECONOMIC DEVELOPMENT - Sayfiyev Jasur Ravshanovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the introduction and development of the digital economy in our country, its importance in the economy and the reforms carried out in this regard.